2019
DOI: 10.46496/medula.v6i2.6728
|View full text |Cite
|
Sign up to set email alerts
|

Konsumsi Makanan Ibu Hamil Berhubungan dengan Berat Badan Lahir Bayi di Daerah Pesisir

Abstract: Background: Low nutritional intake during pregnancy and nutritional status of pregnant women cause various effects for mother and babies. One of the effects is low birth weight. The prevalence of LBW in coastal areas is still high. This study aims to determine the relationship between eating habits of pregnant women with birth weight in coastal areas.Method: This study was an observational analytic study using a cross-sectional method. The sample were 50 respondents obtained using the consecutive sampling meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Research by Kamaluddin, R., et al (2019) discovered that insufficient ANC is linked to an increased risk of LBW. Saimin & Amalia (2019) also demonstrated that insufficient intake of macronutrients during pregnancy can elevate the risk of LBW in newborns.…”
Section: Discussionmentioning
confidence: 93%
“…Research by Kamaluddin, R., et al (2019) discovered that insufficient ANC is linked to an increased risk of LBW. Saimin & Amalia (2019) also demonstrated that insufficient intake of macronutrients during pregnancy can elevate the risk of LBW in newborns.…”
Section: Discussionmentioning
confidence: 93%
“…This was similar with previous study, which found that one of the risk factors for malnutrition was LBW. LBW caused imperfect anatomical and physiological conditions that affect (Saimin, Faisal, Asmarani, & Wicaksono, 2019). Weight gain during pregnancy occurs due to fetal growth, placenta and changes of maternal metabolic.…”
Section: Resultsmentioning
confidence: 99%
“…This is likely cause less weight gain during pregnancy which can give birth to babies with low birth weight. [20].…”
Section: Discussionmentioning
confidence: 99%